Hubungan Tingkat Pencahayaan, Kelembaban Udara, dan Ventilasi Udara dengan Faktor Risiko Kejadian TB Paru BTA Positif di Desa Jatikalang Kecamatan Krian Kabupaten Sidoarjo - sahadewa, sukma; Eufemia, Eufemia; Edwin, Edwin; Niluh, Niluh; Shita, Shita (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2019)
Tuberculosis is an infectious disease caused by Mycobaterium tuberculosis which can be influenced by several factors. The physical condition of an unhealthy home environment plays an important role in the transmission and proliferation of Mycobacterium tuberculosis. The aim of the study was to analyzed the relationship between lighting levels, air humidity, and air ventilation with risk factors for positive Acid resistant bacteria pulmonary TB incidence in Jatikalang Village, Krian District, Sidoarjo Regency. The population of the cases in this study were all patients who were declared positive result of Acid resistant bacteria pulmonary tuberculosis who came to the Krian Health Center for the period January 2017 - December 2017 with a sample size of 34 respondents. The data analysis was used is the odds ratio test. The results of the analysis showed that there was a significant relationship between home ventilation and the incidence of tuberculosis with p-value = 0.006 (<0.05) and OR = 7.800 (> 1) are obtained. The result showed that poor home ventilation has a risk of 7,800 times greater to experience the incidence of pulmonary TB.